DESIGNING AN ARTBOOK OF RATU KALINYAMAT’S STORY AS A VISUAL REPRESENTATION OF HISTORICAL STRUGGLES - Indra Kusuma, Dhany; Haryanto, Eko (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Indonesia, as a country with a rich historical and cultural heritage, has many essential figures whose roles have not been fully documented visually. One of them is Ratu Kalinyamat, a 16th-century female leader renowned for her bravery, wisdom, and determination, as well as her efforts to uphold the sovereignty of Nusantara. The lack of visual representation of this figure in popular media serves as the main background for the design of the art book about Ratu Kalinyamat's story. The creative process involves observation, literature studies, and interviews, resulting in a visual concept that combines narrative illustrations, colour palettes, typography, and layouts that support the storyline. This art book presents eight main scenes from the queen's life journey, ranging from her background and leadership period to her struggles against colonialism, aiming to serve as both a historical educational medium and a means of appreciating visual art.